Replication of a cognitive behavioral therapy for chronic pain group protocol by therapists in training. Issue 2 (June 2014) - Cosio, David
Abstract: According to the American Psychological Association (Division 12), there is strong, long-standing research support for cognitive behavioral therapy (CBT) to treat chronic pain. Furthermore, meta-analytic comparisons have shown CBT to be highly efficacious. However, not all researchers agree with this conclusion. The purpose of the current pilot study was to determine whether a CBT outpatient, group-based treatment facilitated by junior therapists benefited veterans who suffer from mixed idiopathic, chronic, noncancer pain, thus replicating results from effective CBT programs from the past. A sample of 46 veterans aged 33 to 81 years with chronic, noncancer pain who participated in an outpatient CBT pain group therapy protocol at a Midwestern Veterans Affairs Medical Center between November 3, 2009, and September 2, 2010 was evaluated. All participants completed a pre- and postintervention assessment. Paired-samples t tests were conducted to evaluate the impact of the program on veterans' scores on assessment measures. No significant difference was found between the pre- and posttest primary outcome measures of pain intensity. A significant difference was established between the pre- and posttest secondary outcome measure of catastrophizing. However, there were no other significant differences found among the remaining pre- and posttest secondary outcome measures of pain interference, disability, and psychological distress. Training junior therapists on how to use CBT protocols may be enhanced by paying greater attention to what mechanisms are responsible for the desired outcomes among veterans with chronic pain.